1999
DOI: 10.1044/jslhr.4206.1367
|View full text |Cite
|
Sign up to set email alerts
|

A Longitudinal Investigation of Speaking Rate in Preschool Children Who Stutter

Abstract: Both clinical and theoretical interest in stuttering as a disorder of speech motor control has led to numerous investigations of speaking rate in people who stutter. The majority of these studies, however, has been conducted with adult and school-age groups. Most studies of preschoolers have included older children. Despite the ongoing theoretical and clinical focus on speaking rate in young children who stutter and their parents, no longitudinal or cross-sectional studies have been conducted to answer questio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
111
2
9

Year Published

1999
1999
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(129 citation statements)
references
References 55 publications
7
111
2
9
Order By: Relevance
“…This finding held when rate was measured in either syllables per second or phones per second. Analysis by Flipsen also indicated that the rate values obtained at initial and follow-up testing overall were consistent with findings from cross-sectional studies of typically developing children when measured in syllables per second (Amster, 1984;Hall, Amir, & Yairi, 1999;Haselager, Slis, & Rietveld, 1991;Kowal, O'Connell, & Sabin, 1975;Pindzola, Jenkins, & Lokken, 1989;Walker, Archibald, Cherniak, & Fish, 1992). Relative to the phones per second measure, comparisons for the initial testing data indicated slower articulation rates being produced by the current study participants; no direct comparisons were possible for the follow-up data.…”
Section: Articulation Rate and Normalization Failuresupporting
confidence: 61%
See 1 more Smart Citation
“…This finding held when rate was measured in either syllables per second or phones per second. Analysis by Flipsen also indicated that the rate values obtained at initial and follow-up testing overall were consistent with findings from cross-sectional studies of typically developing children when measured in syllables per second (Amster, 1984;Hall, Amir, & Yairi, 1999;Haselager, Slis, & Rietveld, 1991;Kowal, O'Connell, & Sabin, 1975;Pindzola, Jenkins, & Lokken, 1989;Walker, Archibald, Cherniak, & Fish, 1992). Relative to the phones per second measure, comparisons for the initial testing data indicated slower articulation rates being produced by the current study participants; no direct comparisons were possible for the follow-up data.…”
Section: Articulation Rate and Normalization Failuresupporting
confidence: 61%
“…No studies could be identified that have addressed this question. In an analogous study of preschool children who stutter, Hall et al (1999) compared articulation rate data obtained longitudinally from 8 children whose stuttering had recovered against comparable data obtained from 8 children whose stuttering persisted and from a group of 8 typically developing children. The groups did not differ significantly on articulation rate at any of the three test times reported (initial visit, 1 year follow-up, 2 year follow-up) when rate was measured in syllables per second.…”
Section: Articulation Rate and Normalization Failurementioning
confidence: 99%
“…What is measured may also make a difference. One longitudinal study examined speech rates in children whose stuttering would persist over time, in those whose stuttering would remit, and in normally fluent children (Hall, Amir, & Yairi, 1999). Looking at perceptually fluent utterances, Hall and colleagues found no significant differences in the three groups over time in terms of articulation rate measured in syllables per second.…”
Section: The Measurement Of Articulation Rate and Its Effects On Disfmentioning
confidence: 99%
“…Therefore, the articulation rate of the sample utterance was 3.5487 syllables per second (overall duration of perceptually fluent speech (2.53615 sec) ÷ number of syllables (9) = 3.5487 SPS). Simultalk, unintelligible talk, or utterances less than three consecutive words were excluded (Hall, Amir, & Yairi, 1999;Logan & Conture, 1995;Yaruss, 1997;Yaruss & Conture, 1995). The mean number of utterances analyzed for each child was 33.5 (SD = 4.03) for Section A, and 33.79 (SD = 7.44) for Section B, and overall, 942 utterances (508 perceptually fluent utterances, 328 utterances including stuttering-like disfluencies, and 106 utterances including other disfluencies) were analyzed for the articulation rate.…”
Section: 22mentioning
confidence: 99%
See 1 more Smart Citation